Mechanism of Bazedoxifene/conjugated estrogens drugs therapy and its Clinical effect on osteoporosis - Xu, Jiancheng; Ji, Jing; Wang, Zhan; Xu, Tao (Progress in Nutrition, 2021)
Objective: To observe the clinical effects and explore the mechanism of Bazedoxifene/conjugated estrogens upon bone targeting in the treatment of postmenopausal osteoporosis. Methods:The study group was inclusive of 211 postmenopausal osteoporotic patients who were under treatment with Bazedoxifene/conjugated estrogens drugs in the study hospital during the period January and December 2018. The control group contained 56 patients and were treated only with calcium. The researchers analyzed the risks involved in the adverse events such as bone mineral density, osteoprotegerin (OPG) and insulin-like growth factor (IGF) and fracture prior to and after the treatment. Results:The study results inferred that the clinical treatment effective rate was 88.39% in Study group whereas it was 23.21% in the control group and were statistically significant (P＜0.05). Prior to treatment, the researchers identified no significant difference in mean lumbar positive position (L2-4) and right femoral neck bone density IL-1β in between the groups (P>0.05). However, after the treatment, the study group data showed high mean lumbar positive position (L2-4) and heavy right femoral neck bone density in comparison with the control group (P